Journalistic monitoring and privilege in the era of new telecommunications technologies under the Convention on Human Rights and Fundamental Freedoms and the Constitution of the Republic of Poland - Podkowik, Jan (2015)
The digital age has reconfigured the security services, especially the forms of mass surveillance aimed at preventing various threats to society. However, this scenario may become problematic from the perspective of protecting the freedom of the media and journalistic privilege. The author of this article offers an overview of the scope of the protection of the journalistic privilege pursuant to the European Convention for the Protection of Human Rights and Fundamental Freedoms, as well as its management in Poland from the developments prepared by its Constitutional Court.